On the estimation of error terms in the integral asymptotic laws for arithmetic functions - Manstavičius, E. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Манставичюс. К оценке остаточного члена в интегральных асимптотических законах арифметических функций E. Manstavičius. Liekamojo nario integraliniuose asimptotiniuose aritmetinių funkcijų pasiskirstymo dėsniuose įvertinimo klausimu